Rewrite the following equation in slope-intercept form.

y − 6 = 10(x − 9)

1 answer

To rewrite the equation \( y - 6 = 10(x - 9) \) in slope-intercept form (which is \( y = mx + b \), where \( m \) is the slope and \( b \) is the y-intercept), follow these steps:

  1. Distribute the 10 on the right side of the equation: \[ y - 6 = 10x - 90 \]

  2. Add 6 to both sides to isolate \( y \): \[ y = 10x - 90 + 6 \] \[ y = 10x - 84 \]

So, the equation in slope-intercept form is: \[ y = 10x - 84 \]